Job attraction and career choice motivation in a socialist-market economy: the case of the young Vietnamese workforce. Issue 1 (2nd January 2021) - Phan, My Dung; Bae, Yooil
ABSTRACT: This paper aims to explain the career choice motivation of young workers in a non-Western setting, Vietnam. After witnessing the greater role of the relatively small but competent bureaucracy in East Asia, many have assumed that 'pervasive and powerful' bureaucracy also occupies a similar prestigious position in the rapidly growing Vietnam. For the past decade, however, declining talent acquisition in the public sector indicates that good quality workers are leaving or not choosing public sector jobs. What job motivators and perception on the government jobs affect the younger generation's career choice in Vietnam? Based on the classic motivation theories and Public Service Motivation (PSM) framework, we surveyed fresh graduates and final year university students ( n  = 433) and found that there is a positive relationship between public career choice and motivation to serve the public as PSM theory expected. Yet, our data show that traditional job motivators such as materialistic benefits, job security, and stability were more important for the young Vietnamese. From a comparative perspective, this suggests that Vietnamese bureaucracy, regardless of its power and pervasiveness, needs substantial improvement by meeting public workers' basic sanitation needs and working environment to recruit quality manpower for continuous economic success.